A comparative study of watermarking techniques in spatial and frequency domains - Ali Alamari, Abduladhim Mohamad (2014)
The watermarking technique has served as a tool for the protection of Intellectual Property Rights (IPR) of multimedia contents. Due to the digital nature of multimedia documents, these documents can be duplicated, modified, transformed, and diffused very easily. As a result, a watermark that is embedded into the digital data cannot be distinguished from the data itself. Upon request, the watermark can be extracted to prove authorized ownership. In this research, an integration of two watermarking techniques; spatial Least Significant Bit (LSB), and frequency domains Discrete Wavelet Transform (DWT) in cover image, had been proposed. A simulation of the proposed method was done in order to determine the robustness and imperceptibility of the watermarked image when exposed to various attacks. The simulation of the proposed method was done in MATLAB, using the PSNR, MSE, and SSIM, as simulation parameters. The efficiency of the method that was based on the robustness and imperceptibility of the watermarked image was determined through the values of the PSNR, MSE, and SSIM. The PSNR of the LSB, the DWT, and the proposed method were 33.09%, 32.3%, and 34.6 respectively, and the MSE of the LSB, the DWT, and the proposed method were 34.4%, 44.9%, and 20.7% respectively. The findings showed that the proposed method was more efficient in terms of robustness and imperceptibility for the watermarked image, compared to LSB and DWT techniques.